2008
DOI: 10.1063/1.2997345
|View full text |Cite
|
Sign up to set email alerts
|

Single-chain dynamics in a homogeneous melt and a lamellar microphase: A comparison between Smart Monte Carlo dynamics, slithering-snake dynamics, and slip-link dynamics

Abstract: We investigate the ability of Monte-Carlo algorithms to describe the single-chain dynamics in a dense homogeneous melt and a lamellar phase of a symmetric diblock copolymer. A minimal, coarse-grained model is employed that describes connectivity of effective segments by harmonic springs and where segments interact via soft potentials, which do not enforce noncrossability of the chain molecules. Studying the mean-square displacements, the dynamic structure factor, and the stress relaxation, we show that local, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
102
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 74 publications
7
102
0
Order By: Relevance
“…This might be the reason for the retardation compared to the disordered or mixed state. These results are in accordance with recent Monte Carlo simulations based on both the slithering-snake dynamics and the slip-link dynamics, 34 where it has been shown that self-diffusion is coupled in the parallel and perpendicular directions, and they predicted a significant slowing down of the dynamics in the lamellar phase compare to the homogeneous melt. Rheology experiments presented in Figure 7 of the sample at selected temperatures after time-temperature-superposition (tT) of the high-ω data show that there is a clear change in the behavior below and above the T DOT .…”
Section: Resultssupporting
confidence: 92%
“…This might be the reason for the retardation compared to the disordered or mixed state. These results are in accordance with recent Monte Carlo simulations based on both the slithering-snake dynamics and the slip-link dynamics, 34 where it has been shown that self-diffusion is coupled in the parallel and perpendicular directions, and they predicted a significant slowing down of the dynamics in the lamellar phase compare to the homogeneous melt. Rheology experiments presented in Figure 7 of the sample at selected temperatures after time-temperature-superposition (tT) of the high-ω data show that there is a clear change in the behavior below and above the T DOT .…”
Section: Resultssupporting
confidence: 92%
“…The simulation data of the stress autocorrelation for the model without slip-links nicely agree with the prediction of the Rouse-model. In the case of slip-links, one can clearly observe a plateau in an intermediate time regime, which characterizes the elastic properties of the entangled macromolecular fluid in this time window [146,149]. In the simulations, we used N sl = n SL /n = 32 slip-links per chain, and we observe a plateau value of the stress…”
Section: Eo /(N K B T )mentioning
confidence: 99%
“…In our simulation the average distance between slip-links is 4 coarse-grained segments, i.e., n SL = nN/4 [149]. If we decreased the number of slip-links further or decreased a, the tube would become "tight" and the Rouselike motion inside the tube could not be observed.…”
Section: Crossability Of Polymersmentioning
confidence: 99%
See 2 more Smart Citations